Effect of particle size on xylose, glucose and arabinose production from oil palm trunk - Syahirah, Razib (2013)
Oil palm trunks are one of the potential lignocellulosic sources for monosaccharides production.Acid hydrolysis and enzymatic hydrolysis method were combined to obtain higher yield of monosaccharides.Therefore,this paper was designed to study the effect of particle size of oil palm trunk (OPT) on the production of xylose,glucose and arabinose.In acid hydrolysis, 3.24% sulphuric acid (H2SO4) was used at temperature of 121°C for 40 minutes to degrade the hemicelluloses thus generates xylose.The filtrate was analysed using High Performance Liquid Chromatography (HPLC).The result showed that the highest xylose, glucose and arabinose generated were 14.092 g/L, 10.233 g/L and 4.761 g/L respectively at 160μm particle size.Solid wastes from acid hydrolysis were degraded by cellulotic enzyme to produce glucose and the hydrolysate was analysed using YSI Biochemistry Analyser.The highest glucose produced was 2.82 g/L at 800μm particle size.Overall, the highest glucose production was 12.873 g/L at 160μm particle size. As the conclusion, combination of both methods helps in increasing the glucose production and reduces the abundant waste of biomass.From this research,it is recommended that purification method should be done in order to obtain high purity of xylose,glucose and arabinose